2017
DOI: 10.1111/1749-4877.12234
|View full text |Cite
|
Sign up to set email alerts
|

Photokinesis and Djopsin gene expression analysis during the regeneration of planarian eyes

Abstract: Planarians provide the ideal model for studying eye development, with their simple eye structure and exceptionally rapid regeneration. Here, we observed the eye morphogenesis, photophobic behavior, spectral sensitivity and expression pattern of Djopsin in the freshwater planarian Dugesia japonica. The results showed that: (i) Djopsin encoding the putative protein belonged to the rhabdomeric opsins group and displayed high conservation during animal evolution; (ii) planarians displayed diverse photophobic respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…These results suggest that DjMeis1 is required for the differentiation of eye progenitor cells expressing Djovo , and in turn, the formation of eye progenitor cells promote the expression of DjMeis1 . Furthermore, to examine whether the differentiation from eye progenitor cells into mature eye cells was also affected after knockdown of DjMeis1 , we detected the formation of mature eye cells by WISH for opsin [ 41 , 45 ]. We observed that no mature eye cells were regenerated in DjMeis1 RNAi animals at 7 dpa ( Figure 2 E), indicating that DjMeis1 also played an important role in the formation of mature eye cells from eye progenitor cells.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that DjMeis1 is required for the differentiation of eye progenitor cells expressing Djovo , and in turn, the formation of eye progenitor cells promote the expression of DjMeis1 . Furthermore, to examine whether the differentiation from eye progenitor cells into mature eye cells was also affected after knockdown of DjMeis1 , we detected the formation of mature eye cells by WISH for opsin [ 41 , 45 ]. We observed that no mature eye cells were regenerated in DjMeis1 RNAi animals at 7 dpa ( Figure 2 E), indicating that DjMeis1 also played an important role in the formation of mature eye cells from eye progenitor cells.…”
Section: Resultsmentioning
confidence: 99%